Congenital tubular duplication of colon in an adult presented by abdominal pain and constipation: a case report and review of the literature - Sotoodehnia, Saman; Azizi, Rasoul; Darabi, Mohammad Esmaeil; Moazzami, Bahram; Jesmi, Fatemeh; Sheikhvatan, Mehrdad (Iranian Red Crescent medical journal, 2018)
Introduction: Congenital duplications of the intestinal tract are rare diseases, observed mainly in ileum and stomach, while less than 7% of cases occur in the colon. They are mainly diagnosed during early childhood, while few cases may remain asymptomatic until adulthood. Case Report: We present a 31-year-old female with chronic abdominal pain without significant past medical history. Pre-operative diagnosis was an enterocolic fistula, which was considered after colonoscopy. Abdominal surgery with midline incision was performed for the patient with suspicion of congenital colon anomaly. During the surgery, the surgeon found an additional colon closed loop that originated from the posterior aspect of the transverse colon and was attached posteriorly to the sigmoid colon. Microscopic examination revealed tubular duplication of the colon with marked dilatation, focal mucosal ulceration, granulation tissue, and mild chronic nonspecific inflammation. Discussion: As congenital duplication of colon is a rare condition with non-specific clinical symptoms, high suspicion of the physician and thorough examination can help the diagnosis and surgical treatment as soon as possible to stop patients’ pain and associated problems.
Gesehen am 30.03.2020